How relative age effects associate with football players`market values: Indicators of losing talent and wasting money - Romann, M.; Javet, M.; Cobley, S.; Born, D.-P. (Sports, 2021)
Background: In football, annual age-group categorization leads to relative age effects(RAEs) in talent development. Given such trends, relative age may also associate with market values.This study analyzed the relationship between RAEs and market values of youth players. Methods:Age category, birthdate, and market values of 11,738 youth male football players were obtainedfrom the "transfermarkt.de" database, which delivers a good proxy for real market values. RAEswere calculated using odds ratios (OR) with 95% confidence intervals (95%CI). Results: SignificantRAEs were found across all age-groups (p< 0.05). The largest RAEs occurred in U18 players (Q1[relatively older] v Q4 [relatively younger] OR = 3.1) ORs decreased with age category, i.e., U19(2.7), U20 (2.6), U21 (2.4), U22 (2.2), and U23 (1.8). At U19s, Q1 players were associated withsignificantly higher market values than Q4 players. However, by U21, U22, and U23 RAEs wereinversed, with correspondingly higher market values for Q4 players apparent. While large typicalRAEs for all playing positions was observed in younger age categories (U18-U20), inversed RAEswere only evident for defenders (small-medium) and for strikers (medium-large) in U21-U23 (notgoalkeepers and midfielders). Conclusions: Assuming an equal distribution of football talent existsacross annual cohorts, results indicate the selection and market value of young professional playersis dynamic. Findings suggest a potential biased selection, and undervaluing of Q4 players in youngerage groups, as their representation and market value increased over time. By contrast, the changingrepresentations and market values of Q1 players suggest initial overvaluing in performance andmonetary terms. Therefore, this inefficient talent selection and the accompanying waste of moneyshould be improved.